Nghị quyết Miễn nhiệm chức vụ Tổng Thư ký Quốc hội khóa XIV (Nghị quyết số: 147/2021/QH14) - Quốc hội (2021)
Toàn văn Nghị quyết Miễn nhiệm chức vụ Tổng Thư ký Quốc hội khóa XIV (Nghị quyết số: 147/2021/QH14)